A strategic approach developing an Interactive Multimedia Learning System for young learners (learning Malay proverb) / Zatul Saliza Saleh - Zatul Saliza, Saleh (2006)
Research conducted by local linguistic shows that the grasp of Malay Proverbs among younger generation is deteriorating. This dissertation proposes a strategic approach to learn Malay proverbs through interactive multimedia learning system for young learners. This approach employs effective learning strategy that proves its usability to help young learners understand and remember better. The arrangement of how young learners' mind work reflect the stages of human cognition: immediate apprehension, abstract thinking and practice. The three stage are formulated into three step approach: knowing, understanding and usage. All these three stages are then used to create instructional objective, content and the test items by using rapid prototyping model. Appropriate user interface design was created based on the storyboard. After the implementation, final evaluation was conducted using two methods. The predictive evaluation was conducted by allowing a multimedia designer to use the system. It was concluded that more extensive instructions are needed in order to let the system to be 100% independent. The observing and monitoring usage method showed that 70% of the young learners could perform each task smoothly. The remaining 30% could perform it after they finished the first two units. The system was also evaluated on its learning strategy. 80% of the students found that the three steps approach was easy to follow while the remaining 20% could cope after further elaboration was given.